2021
DOI: 10.3390/pathogens10081017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disinfection with Chlorine Dioxide on Respiratory Transmitted, Enteric, and Bloodborne Viruses: A Narrative Synthesis

Abstract: A viral spread occurrence such as the SARS-CoV-2 pandemic has prompted the evaluation of different disinfectants suitable for a wide range of environmental matrices. Chlorine dioxide (ClO2) represents one of the most-used virucidal agents in different settings effective against both enveloped and nonenveloped viruses. This narrative synthesis is focused on the effectiveness of ClO2 applied in healthcare and community settings in order to eliminate respiratory transmitted, enteric, and bloodborne viruses. Influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Chlorine dioxide is often used in the treatment of water and wastewater due to its virucidal effect as it causes disruption of viral glycoproteins including viral genome (Ge et al, 2021 ). It is also used as an alternative disinfectant to chlorine and has been shown to be effective against both enveloped and non‐enveloped viruses (Ge et al, 2021 ; Totaro et al, 2021 ). However, limited studies have evaluated the effect of chlorine dioxide as an option to decrease the viral titers in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorine dioxide is often used in the treatment of water and wastewater due to its virucidal effect as it causes disruption of viral glycoproteins including viral genome (Ge et al, 2021 ). It is also used as an alternative disinfectant to chlorine and has been shown to be effective against both enveloped and non‐enveloped viruses (Ge et al, 2021 ; Totaro et al, 2021 ). However, limited studies have evaluated the effect of chlorine dioxide as an option to decrease the viral titers in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…This activity was shown at the patient chair point (1 m from aerosolization source). Considering the mean chlorine values reached in air, O-CD method may prevent the microbiological risk done by environmental bacteria and respiratory viruses transmitted by droplets (SARS-CoV-2) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ClO 2 prevents the recombinant spike protein of severe acute respiratory syndrome coronavirus 2 by attaching to its receptor, angiotensin-converting enzyme 2 [12,13]. Additionally, ClO 2 interacts with one or more cysteine, tyrosine, or tryptophan amino acid residues of the spike proteins in enveloped viruses and also attaches to the viral DNA of non-enveloped viruses [14,15]. However, the concentration, exposure time, pH, and temperature affect the antiviral and antimicrobial effects of ClO 2 [16][17][18].…”
Section: Discussionmentioning
confidence: 99%